Normalization and its Discontents : Constructing the 'Irreconcilable' Female Political Prisoner in Northern Ireland - Corcoran, Mary (The British journal of criminology, 2007)
This article accounts for the official construction of women political prisoners as the intractable and problematic subjects of political decarceration in Northern Ireland. The discussion firstly locates the processes of penal normalization' in Northern Ireland in a hegemonic struggle which preceded the managerialist era usually associated with political decarceration. Secondly, it traces the emergence of ideal-typical sites of negotiation and contestation between women political prisoners and the authorities. Thirdly, it utilizes feminist critiques of contemporary penal governmentalities to identify the formation of politico-gendered penal controls, concluding with summary of the era's punitive excesses with respect to women prisoners